THE EFFECTIVENESS OF READ, COVER, REMEMBER, RETELL (RCRR) STRATEGY FOR TEACHING READING COMPREHENSION - Novrisal Wadi; Citra Kusumaningsih; Maliqul Hafis (IKIP PGRI Pontianak, 2020)
The purpose of this research were to find out whether there was difference of students reading comprehension achievement before and after the implementation Read, Cover, Remember, Retell (RCRR) strategy and how strong is the effect of Read, Cover, Remember, Retell (RCRR) strategy on reading comprehension to the eighth grade students of SMPS Harapan Ananda Sungai Raya in the Academic Year of 2019/2020.The design was a pre-experimental research in form of one group pre-test post-test design. The population of this research was all of the eighth grade students of SMPS Harapan Ananda Sungai Raya in the Academic Year of 2019/2020 and the sample chosen was VIII A which consisted of 44 students. The sample was examined with cluster random sampling technique. The research was conducted at SMPS Harapan Ananda Sungai Raya. The technique of data collection applied in this research was measurement technique and analyzed by SPSS 17.0 version. The data were collected through multiple choice test. The pre-test and post-test were conducted in order to collect the data from the students. The researcher used the data distribution. Since the data was normal the researcher used paired sample test analysis to test the hypotheses and used Cohen’s effect size to test the effect of the use of Read, Cover, Remember, Retell (RCRR) strategy. The research finding showed that Read, Cover, Remember, Retell (RCRR) strategy was effective on reading comprehension, it was proved by the mean score during pre-test and post-test were 30.82 and 49.34 which meant that there were difference before and after treatment. The SD of pre-test (9.933) was higher than SD of post-test (8.768). It showed that the treatment was well implemented. Lastly it was proved by paired sample t-test value, sig value was smaller than α (0,00 0,05) which meant that Ha was accepted. The effect of the use Read, Cover, Remember, Retell (RCRR) strategy was moderate effect level based on the Cohen’s effect. It was 0.99 which meant that RCRR strategy gave positive effect to students’ reading comprehension. Keywords : RCRR Strategy, Reading Comprehension, Pre-Experimental Research.